Advanced Glycation End-Product (AGEs)Level in a Diabetic Rat Model Treated with Warfarin Anticoagulant - Musyarrafah; Halia Wanadiatri; I G.A. Adnyana (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Diabetes mellitus is a chronic disease that is the most seriously cause of macrovascular and microvascular complications that threaten life , expensive and reduces life expectancy. The occurence of cell damage and inflammation due to AGEs and RAGE reactions generally exacerbates the risk of macrovascular complications . Pharmacological therapy given to prevent these complications is the warfarin anticoagulant . the duration of warfarin use can increase the hardening of blood vessels or vascular calcification and is compounded by AGEs accumulation and RAGE activation. Objective: To analyze plasma AGE levels as a risk factor for vascular calcification in DM and non-DM rats models treated with warfarin anticoagulants. Method: This study used a Quasi experimental method with a posttest only control group design. The total sample was 28 samples divided into 4 groups, each group consisting of 7 rats grouped into DM + Aquadest group, DM + Warfarin group, non-DM + Aquadest group , and non-DM + Warfarin group. Plasma AGE levels were measured using the ELISA method and the results were analyzed using Anova. Results: AGE Level in the DM + Warfarin group (Mean= 1.183; SD=0.16) was slightly high than AGE level in normal rat group with Warfarin induction (Mean=1,012; SD=0,02). In the normal rat group treated with Aquadest was slightly low than AGE level in the DM rat group with warfarin induction (Mean=1.147; SD=0.13). Interestingly, There was no difference in plasma AGE levels between groups (p=0,155). Conclusion: AGE levels at the onset of DM are not yet able to progressively activate vascular damage through the AGE/RAGE signaling pathway.